Analysis of the influence of social media marketing on brand awareness and brand loyalty: the mediating role of brand gestalt (study at PT AKR Land Kawanua Emerald City Manado) - Mokalu, Risca Rioline; Soewignyo, Tonny Irianto (Jurnal Mantik, 2024)
This research was conducted with the aim of knowing how far and how effective the use of social media is in marketing AKR Land Kawanua Emerald City products. And can this marketing strategy strengthen the brand of the Kawanua Emerald City project so that it can escape the shadow of the sister project when introducing it to consumers. The chosen research design is a case study qualitative research approach, which aims to understand and explain the influence of Social Media Marketing. In this case study research, the research informant is the Kawanua Emerald City Sales & Marketing team who are the primary data source and for secondary data will use company data starting from reports on the use of social media tools in marketing and implementing other strategies. Based on the hypothesis testing that has been done, it can be concluded with several results that Social Media Marketing variables have no influence on brand gestalt, but Social Media Marketing variables have an influence on brand awareness and brand loyalty. Furthermore, the variable brand gestalt has no effect on brand awareness, but has an influence on brand loyalty among employees of PT AKR Land Kawanua Emerald City Manado. Finally, the results of the study found that brand awareness had no effect on brand loyalty among PT AKR Land Kawanua Emerald City Manado employees